Rumi's thought and its relation to the creation of the architect - yousef goudarzi (مطالعات ادیان و عرفان تطبیقی, 2022)
Architecture is a phenomenon related to man and must be realized with him, so addressing the subject of man as a basic knowledge in the process of creation of the architect, is undeniable. In this regard, understanding the levels of architecture in relation to the levels of human existence will be very important. On the other hand, since the definition of man and his perceptions of him are sometimes very different, differences in the understanding of architecture will also be very natural. To understand creativity in architecture that is in line with the culture, religion and art of Iran and at the same time can be related to modern knowledge, a study of the works and ideas of Rumi will be helpful. Mysticism is closely related to the art of architecture. Mystical views and thinking are beyond time and space, so it can encompass the history and geography of the universe. He was not an architect theorist; But in his wonderful work, Masnavi has paid attention to architecture for various reasons, explicitly or implicitly, intentionally or unintentionally. This feature can be seen several times: informing about the world of architecture in which he lived; Using architectural forms of imagination in speech; Establishing a relationship between architecture and existence; Provide general ideas that can be extended to architecture; Invitation to the remembrance of God through architecture In this journey, we try to understand the understanding of creationism in architecture through Rumi's thoughts.